Reappraisals and new studies of the modern Jewish experience : essays in honor of Robert M. Seltzer - Smollett, Brian M.; Wiese, Christian (Brill reference library of Judaism., 2014)
Reappraisals and New Studies of the Modern Jewish Experience provides a variety of new perspectives on several central questions in Jewish intellectual, social, and religious history from the eighteenth century to the present.